Hubungan Kecerdasan Interpersonal Guru Dengan Komunikasi Pembelajaran Kelompok A Di TK Se-Kelurahan Pabelan Kartasura Sukoharjo - Inayati, Azizah Surya; , Dr. Darsinah, M.Si (2016)
The purpose of this research to know the correlation between interpersonal intelligent and learning communication. The research design is descriptive correlational. Population of the research amount 42 teachers. The sample is 14 teachers, the method is Probability Sampling with Stratified Sampling. Collection technik by questionnaire. This research use correlation product moment for the analysis method. According to correlation analysis the result is r product moment= 0,735 and the value of significance= 0,003 (p < 0,01). It means that research have a positive correlation and this correlation is significant. The conclusion is there is positive correlation significant characteristic between interpersonal intelligent and learning communication.